Recent advances of lysine lactylation in prokaryotes and eukaryotes - Zhao, Wenjuan; Xin, Jiayi; Yu, Xin; Li, Zhifang; Li, Nan (Frontiers in Molecular Biosciences, 2025)
Lysine lactylation is a newly discovered protein post-translational modification that plays regulatory roles in cell metabolism, growth, reprogramming, and tumor progression. It utilizes lactate as the modification precursor, which is an end product of glycolysis while functioning as a signaling molecule in cells. Unlike previous reviews focused primarily on eukaryotes, this review aims to provide a comprehensive summary of recent knowledge about lysine lactylation in prokaryotes and eukaryotes. The current identification and enrichment strategies for lysine lactylation are introduced, and the known readers, writers, and erasers of this modification are summarized. In addition, the physiological and pathological implications of lysine lactylation are reviewed for different organisms, especially in prokaryotic cells. Finally, we end with a discussion of the limitations of the studies so far and propose future directions for lysine lactylation investigations.